THE CONTRIBUTIONS OF SCIENTIFIC PRODUCTIONS IN THE AREA OF NURSING AND ENVIRONMENT: A NARRATIVE REVIEW - Peres, Roger Rodrigues; Camponogara, Silviamar; Soares, Sabrina Gonçalves Aguiar; Diaz, Paola da Silva (Journal of Health Care, 2015)
Introduction: Society is under an environmental crisis that affects directly human life and therefore demandsthe nursing area to comprehend the relationship that exists between health and environment to beable to face the new demands that are present in this environmentally disturbed scenery. Aim: To describethe contributions of scientific productions about the nursing area concerning the environment. Method:This is a qualitative and descriptive study, characterized as a narrative literature review. The researcheddatabases were the Nursing Database, the Latin-American and Caribbean Literature on Health Sciencesand the Medical Literature Analysis and Retrieval System Online through the use of the following descriptors:"nursing", "environmental education", "environment", "ecology", "environmental health", and"sustainable development". The research was carried out in August of 2013 with no demarcation. Results:The articles that compose the corpus show fragile conceptions about the environment and environmentalhealth. They also show concern about the health professionals’ lack of knowledge about the residues of health services and their management, plus the difficulties of multi-professional work about the topic. In terms of professionalformation, different investigations point to the need of a more effective approach about the environmental issues to achieveethical and environmentally responsible awareness. Conclusions: New researches must be done to consolidate the nursingknowledge on the socio-environmental area and also to exploring new conceptions and practices that are present in the nurse’swork, considering the importance of the topic to the formation of environmentally responsible professionals and, consequently,a healthier reality.